The evolution of London's crossrail scheme and the development of the department for transport's economic appraisal methods - Tom Worsley (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
Cost benefit analysis has been used in the United Kingdom for the appraisal of road schemes over the past fifty years. It was less widely used for rail, where most investment was concerned with renewing the existing network. The Central London Rail Study (1988) used cost benefit analysis to address the problem of overcrowding on London's rail network. The Crossrail scheme proposed in the Study was discontinued because of a recession and because of the priority given the developing links to London's Docklands. Progress on Crossrail was resumed in 2002 at the same time as the Department's appraisal methods were being revised to incorporate Wider Economic Benefits. The quantification of these additional benefits, the resolution of a source of funding and the role of the Mayor all influenced the Government's decision that the scheme should be built. Identification of some of the Wider Benefits poses problems for transport models that are only partially resolved through the use of land use transport interaction models. Although the use of a Gross Value Added metric provides an alternative way of estimating the economic impacts of a scheme, it does not replace cost benefit analysis as a decision aid for government ministers.
Keywords: 330